Composition, mixing state and water affinity of meteoric smoke analogue nanoparticles produced in a non-thermal microwave plasma source - Nachbar, Mario; Leisner, Thomas (Zeitschrift für physikalische Chemie, 2018)
The article reports on the composition, mixing state and water affinity of iron silicate particles which were produced in a non-thermal low-pressure microwave plasma reactor. The particles are intended to be used as meteoric smoke particle analogues. We used the organometallic precursors ferrocene (Fe(C5H5)2) and tetraethyl orthosilicate (TEOS, Si(OC2H5)4) in various mixing ratios to produce nanoparticles with radii between 1 nm and 4 nm. The nanoparticles were deposited on sample grids and their stoichiometric composition was analyzed in an electron microscope using energy dispersive X-ray spectroscopy (EDS). We show that the pure silicon oxide and iron oxide particles consist of SiO2 and Fe2O3, respectively. For Fe:(Fe+Si) ratios between 0.2 and 0.8 our reactor produces (in contrast to other particle sources) mixed iron silicates with a stoichiometric composition according to FexSi(1−x)O3 (0≤x≤1). This indicates that the particles are formed by polymerization of FeO3 and SiO3 and that rearrangement to the more stable silicates ferrosilite (FeSiO3) and fayalite (Fe2SiO4) does not occur at these conditions. To investigate the internal mixing state of the particles, the H2O surface desorption energy of the particles was measured. We found that the nanoparticles are internally mixed and that differential coating resulting in a core-shell structure does not occur.
Gesehen am 04.12.2019